GREEN HUMAN RESOURCES MANAGEMENT AND SERVICE QUALITY IN THE UAE ENERGY SECTOR - Rashid, Al Jabri Ahmed Abdallah; Rosdi, Siti Asma’ Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Purpose: The study investigates the impact of green human resources management on the service quality in the UAE energy sector. The study thus examines the extent to which UAE’s energy and power sector adopts Green Human Resources Management and the relationship between Green Human Resources Management and the UAE energy and power sector service quality. Methodology: This is quantitative study with data collected from 1221 respondents using probability sampling approach. Data are collected with a questionnaire and the data gathered through the questionnaire are subjected to descriptive and inferential statistics. Finding(s): The results show that there is a high adoption of Green Human Resource Management (GHRM) methods in the UAE’s energy and power sector and there is significant relationship between the adoption of GHRM and service quality in the sector. Implication: The study concludes by recommending adoption of GHRM in other sectors so as to enhance service quality. Originality/Value: This study adds to the scarce body of research on GHRM in the Middle East by providing empirical support for its applicability in raising service standards in the energy industry. The study is thus important, as it will enable us to understand the crucial relationship between green human resources and service quality.